International handbook of victimology - Shoham, S. Giora, 1929-; Knepper, Paul; Kett, Martin (CRC Press, 2010)
Exploring topics such as conceptions of victimhood, secondary and hidden victimization, and social services for victims along with more recent issues, this handbook deals with the themes such as restorative justice, the use of government-sponsored crime victimization surveys, compensation and restitution schemes, and victims' rights legislation.